2004
DOI: 10.1021/jp037125l
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Fluorescence Quenching of Tyrosine by the Peptide α-Carbonyl Group Revisited

Abstract: The environment-dependent multiexponential behavior of N-acetyltyrosinamide (NAYA) and other tyrosine derivatives is revisited, aiming for a better understanding of tyrosine as an intrinsic fluorescent probe for protein microenvironment changes during conformational changes. The effects of solvent polarity, viscosity, and temperature on the fluorescence decay of NAYA were evaluated using dioxane-water mixtures and pure solvents. Double-exponential decays were observed in dioxane-water mixtures above 70% (v/v) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 26 publications
12
57
0
Order By: Relevance
“…The theory of tyrosyl rotamer interchange and its effect on the fluorescence decay of the tyrosyl residue in small peptides has been described in detail by us and others 23,31,32. That work demonstrates definitively that rotamer interchange occurs on the time scale of the fluorescence decay and must be accounted for to accurately describe the photophysics of Tyr in peptides.…”
Section: Theorymentioning
confidence: 90%
See 1 more Smart Citation
“…The theory of tyrosyl rotamer interchange and its effect on the fluorescence decay of the tyrosyl residue in small peptides has been described in detail by us and others 23,31,32. That work demonstrates definitively that rotamer interchange occurs on the time scale of the fluorescence decay and must be accounted for to accurately describe the photophysics of Tyr in peptides.…”
Section: Theorymentioning
confidence: 90%
“…In order to calculate the FRET efficiency, it was therefore necessary to know the fluorescence lifetime of the energy donor (Tyr) in the absence of FRET. But the Tyr lifetime depends strongly on the Tyr rotameric configuration 23,31,32. Therefore, it was necessary to take into account the rotameric configuration of Tyr (but not of Trp, because it is the energy acceptor and its lifetime was not measured) to determine the FRET rate.…”
Section: Theorymentioning
confidence: 99%
“…26,27 Noronha et al 27 reported that N-acetyltyrosinamide has Φ f ) 0.18 in dioxane, and drops to 0.05 as the water composition of the solvent is increased to 100% at 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare the measured and calculated transfer efficiencies, the individual tyrosine quantum yields must be known. It is possible that some of the tyrosine’s are quenched by interactions with near-by polar groups [35]. For example, in the belayed structure of AB, Tyr 43 is hydrogen-bonded to Lees 30, so it is unlikely to emit.…”
Section: Resultsmentioning
confidence: 99%